Prophylactic Nrf2 Activation Halts Progression of the Severe Adult Phenotype of Sickle Cell Disease in Transgenic Mice - Ghosh, Samit; Ihunnah, Chibueze A.; Hazra, Rimi; Owusu-Ansah, Amma T.; Hansen, Jason M; Archer, David R.; Ofori-Acquah, Solomon Fiifi (Blood, 2015)
Transition from pediatric to adult care is associated with poor prognosis and a sharp rise in mortality in sickle cell disease (SCD). Hitherto, mechanisms that promote the severe adult phenotype of SCD have not been defined. We performed a longitudinal cohort study in thirty-two Townes transgenic mice (SS; n=16, AA; n=16) aged 1 month through to 10 months to identify prognostic factors of SCD severity. Thirty-eight percent of the SS mice died during this period while all the control AA mice survived (Log-rank Mantel Cox test, p<0.01). Hemoglobin (Hb) concentration declined sharply at 3 months in the SS mice while it remained unchanged in the age-matched AA mice. Worsening anemia was concomitant with increased concentrations of multiple markers of intravascular hemolysis including plasma heme (p=0.0019), plasma Hb (p=0.002), and lactate dehydrogenase, LDH (p=0.032) as the SS mice reached adulthood. Collectively, these data identified hemolytic stress as a component of the adult phenotype of SCD. An age-dependent increase in the concentration of vascular cell adhesion molecule-1 (VCAM-1) in the plasma of SS animals (p<0.05), but not in AA mice highlighted vascular inflammation as another component of the severe adult phenotype of SCD. We confirmed the link between age-related disease severity and vascular inflammation by demonstrating a 2-fold higher concentration of vascular endothelial cadherin (sVE-cad) in the plasma of SS mice at 3-months compared to the steady-sate values of the same marker when the mice were one month old (p<0.05). Since nuclear factor erythroid-2 factor 2 (Nrf2) controls the antioxidant response to hemolytic stress, we tested the hypothesis that this factor may influence the progression of SCD. We generated bone marrow chimeric sickle mice devoid of Nrf2 activity in the endothelium and in other non-hematopoietic tissues. The resulting chimeras had markedly more severe intravascular hemolysis and vascular inflammation defined by higher concentrations of sVCAM-1 (p<0.01) and sVE-cad (p<0.01) than age-matched SS mice with a full complement of Nrf2 activity. Next, we determined whether prophylactic activation of Nrf2 in 1 month SS mice would slow down the disease severity seen in adulthood. A group of newly weaned SS mice aged ~1 month were randomized to receive the Nrf2 activator 3H-1, 2-dithiole-3-thione (D3T; n=8), or a DMSO vehicle by oral gavage (0.5 mmole/kg, 3x/week). After eight weeks of treatment the Hb dropped by <2% in the D3T group compared to a 10% drop in the vehicle group. In addition, D3T treatment blunted the age-related worsening of intravascular hemolysis, which we initially observed in the longitudinal cohort, and confirmed in the vehicle treated animals, by the elevations in plasma heme (p<0.01), plasma Hb (p<0.01), plasma bilirubin (p<0.05) and LDH (p<0.05). Remarkably, D3T treatment reduced the mean plasma sVCAM-1 at 3 month (731.8±28.2) from a significantly higher value when the same animals were aged 1 month (882.4±36; p<0.01, n=8), as well as stabilizing the plasma concentration of sVE-cad with aging. On the contrary, both sVCAM-1 and sVE-cad levels rose significantly during the adult transition in the vehicle-treated SS mice (p<0.001). Overall, our data identify Nrf2 as an attractive therapeutic target to slowing down the progression of SCD during the pediatric to adult transition. Archer:Global Blood Therapeutics: Consultancy.